0
$\begingroup$

I came across this simplification in an iTunes U calculus course.

$$\frac{\frac{1}{x_{0}+\delta x}-\frac{1}{x_{0}}}{\delta x} = \frac{1}{\delta x} \left(\frac{x_{0}-(x_{0}+\delta x)}{(x_0+\delta x)x_{0}}\right)$$

I didn't understand how this was done. I can see the denominator being taken out for $\frac{1}{\delta x}$ but do not understand the remainder. Can someone give me some guidance? Thanks

$\endgroup$
  • $\begingroup$ The fractions in the numerator were written with the same denominator $x_0(x_0+\delta x)$. $\endgroup$ – Bernard Oct 29 '16 at 19:07
1
$\begingroup$

It is $$\frac 1a-\frac 1b=\frac{b-a}{ab}.$$ So, if $a=x_0+\delta x$ and $b=x_0$ you have

$$\frac 1{x_0+\delta x}-\frac 1{x_0}=\frac{x_0-(x_0+\delta x)}{x_0(x_0+\delta x)}.$$

$\endgroup$
1
$\begingroup$

Basically it is taking the same denominator: $$\frac1a-\frac1b=\frac{b}{ab}-\frac{a}{ab}=\frac{a-b}{ab}.$$ In the special case $a=x_0$, $b=x_0+\delta x$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.